2019
DOI: 10.3892/ol.2019.9917
|View full text |Cite
|
Sign up to set email alerts
|

E‑cadherin and NEDD9 expression in primary colorectal cancer, metastatic lymph nodes and liver metastases

Abstract: In Croatia, colorectal cancer mortality rates in males are the third highest in Europe, after Hungary and Slovakia. The results for females rank Croatia in second place after Hungary. According to previous studies, the loss of E-cadherin expression and the higher expression of neural precursor cell-expressed developmentally downregulated 9 (NEDD9) are associated with a worse prognosis. The aim of the present study was to analyze the immunohistochemical expression of NEDD9 and E-cadherin as markers of metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 45 publications
8
19
0
Order By: Relevance
“…In a subgroup analysis of patients with and without lymph node metastases, there were no significant differences in Cx43 and NEDD9 expression in patients without lymph node metastases , but patients with lymph node metastases showed higher expression of epithelial NEDD9 (Table 1, Figure 2). (14,(16)(17)(18)(19). Similar as in our study, expression of NEDD9 was found significantly increased in the tissue of pancreatic ductal adenocarcinoma compared to adjacent pancreatic tissue (18), but the same was not established in colorectal cancer (19).…”
Section: Predicting 2-year Survivalsupporting
confidence: 82%
See 1 more Smart Citation
“…In a subgroup analysis of patients with and without lymph node metastases, there were no significant differences in Cx43 and NEDD9 expression in patients without lymph node metastases , but patients with lymph node metastases showed higher expression of epithelial NEDD9 (Table 1, Figure 2). (14,(16)(17)(18)(19). Similar as in our study, expression of NEDD9 was found significantly increased in the tissue of pancreatic ductal adenocarcinoma compared to adjacent pancreatic tissue (18), but the same was not established in colorectal cancer (19).…”
Section: Predicting 2-year Survivalsupporting
confidence: 82%
“…(14,(16)(17)(18)(19). Similar as in our study, expression of NEDD9 was found significantly increased in the tissue of pancreatic ductal adenocarcinoma compared to adjacent pancreatic tissue (18), but the same was not established in colorectal cancer (19).…”
Section: Predicting 2-year Survivalsupporting
confidence: 82%
“…The majority of published studies focused on identifying potential protein biomarkers using immunohistochemistry analysis of tissue samples or using enzyme-linked immunosorbent assay to measure their plasma concentrations. 25,30 Recent attention was given to circulating cell-free nucleic acids (cfNAs), such as DNA, mRNA or microRNA (miRNA), and cellular nucleic acids (cNAs). Currently, the most commonly used methods for cfRNAs and cNAs detection are qRT-PCR, microarray and deep sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 However, there are limited data about EMT genes expression in patients with CRLM. 24,25 Moreover, relation and correlation between EMT genes expression in serum, metastatic CRC tissue or non-tumor liver tissue have been insufficiently investigated. The prognostic value of EMT markers in prediction of rapid disease progression after curativeintent treatment is still not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Jurčić et al, 48 reported no significant differences regarding the expression of E-cadherin in the primary tumor of CRC. Indeed, these results are similar to our own findings in that we did not observe significant differences in CDH1 expression in both AP and HP groups compared with normal participants.…”
Section: Discussionmentioning
confidence: 95%